Pedagogical Innovation in the Conditions of Informatization and Computerization of Humanities Education (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The analysis of the processes associated with the fact that the course of transferring the Ukrainian economy from a raw material development path to an innovative one is extremely important. The authors believe that the role of higher education in this process is key. But it itself is faced with a huge number of problems, one of which is improving the quality of its functioning and guaranteeing the results of its activities. This problem is closely related to the implementation of innovations. The authors suggest that innovation in education should be understood as an innovation designed to resolve the current problem situation in order to optimize the educational process, improve its quality or organize favorable conditions for the assimilation of material by students. Based on a critical approach to reform the current system of higher education the paper touches upon the need to change the process infornatization of humanities education. The authors show that for the realization of a humanitarian approach to the modern educational situation, you must be friendly. The conceptually changing field of modern educational practices, aspirations and attempts to humanize and humanize education, taking into account the realities of the information society are favorable factors in creating and implementing the concept of humanities education, which allows different ways of implementation. The development of humanities education in the information society is aimed at implementing an interdisciplinary approach, i.e. should ensure the effectiveness of the development and application of humanities knowledge and form a conscious responsible choice in a variety of cultural meanings, cultural self-determination.